Causes of Water Management Crisis in Afghanistan - Karimullah Baidar; Ihsanullah Ihsan; Malaly Safi (RIRAI Publisher, 2022)
Water is the common property of all human beings, which must be properly passed on to future generations. Water is one of the biggest challenges of the 21st century and its mismanagement can threaten living Creatures’ lives. Afghanistan is one of the countries in the world that has sufficient water resources but unfortunately its water is not properly managed due to the presence of water along its borders which comp cate water management but some Other factors such as lack of capital, lack of skilled manpower and lack of agreements with the neighboring countries on the water are the factors that are causing water management crisis in the country. The purpose of this article is to explore and investigate the causes the of water management crisis in the country and strive to find out the causes that play an important role in the emergence of water management crisis in the country. This article is a descriptive study of the research approach and its methods analytical.